1998
DOI: 10.1007/s004310050959
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the microdeletion 22q11 in newborn infants with congenital conotruncal cardiac anomalies

Abstract: In 50/104 newborns with conotruncal defects, an interstitial deletion 22q11 was found. Fluorescence in Situ Hybridization should be performed in newborn infants with conotruncal defect and at least one additional manifestation of the CATCH22 phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
2
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 17 publications
2
64
2
5
Order By: Relevance
“…There are several studies on the prevalence of individual chromosomal abnormalities, like 22q11.2 deletions [31][32][33] (velocardiofacial and DiGeorge syndromes are due to 22q11.2 deletions). Borgmann et al 31 found that routine screening for 22q11.2 deletions in nonsyndromic CHD subjects gave no yield.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies on the prevalence of individual chromosomal abnormalities, like 22q11.2 deletions [31][32][33] (velocardiofacial and DiGeorge syndromes are due to 22q11.2 deletions). Borgmann et al 31 found that routine screening for 22q11.2 deletions in nonsyndromic CHD subjects gave no yield.…”
Section: Discussionmentioning
confidence: 99%
“…[53][54][55] Children with double-outlet right ventricle or transposition of the great arteries are rarely found to have a 22q11 deletion (Table 1). 51,[55][56][57][58][59][60][61][62] It is important to identify the cardiac patient with a 22q11 deletion by FISH testing to evaluate for associated noncardiac features of the syndrome in a timely fashion and to offer accurate genetic counseling. Additionally, a higher operative mortality in some individuals with a 22q11 deletion has been documented, 63,64 and the clinician and surgeon should be aware of this when planning surgery and postoperative care, particularly as related to calcium metabolism or immunologic issues.…”
Section: Loci and Genes Associated With Congenital Heart Defects Idenmentioning
confidence: 99%
“…Conotruncal heart defects account for approximately 50 -60% of cardiac malformations diagnosed in the neonatal period (Iserin et al, 1998) and are associated with significantly high morbidity and mortality (Ferencz et al, 1985;Ferencz, 1990). This category includes defects such as truncus arteriosus (TA), double outlet right ventricle (DORV), tetralogy of Fallot (TOF) with or without pulmonary atresia, and interrupted aortic arch (IAA).…”
Section: Introductionmentioning
confidence: 99%